Optical break-down in alkali-haloid single crystals by laser focused radiation: the stage of local thermal explosion - Kononenko, V.G.; Volosyuk, М.А.; Volosyuk, А.V. (Вопросы атомной науки и техники, 2015)
Based on the results of experimental studying the pore formation kinetics and morphology in KCl single crystals under conditions of optical break-down by laser focused radiation were studied. It was shown that with observed parameters of the seats of energetic bursts and the dynamics of their formation, the optical break-down is similar to a powerful point explosion. In the heated area, a shock wave is generated. Having the velocity more than by an order exceeding the acoustic speed, the shock wave comes to the single crystal boundary earlier than other lattice disturbances and initiates formation of crowdions and their movement along atomic close-packed rows parallel to <110> type directions in both sublattices. From the condition of self-consistency between the flows of generated crowdions initiated by the supersonic shock wave and ones passing into unstressed crystal, it follows that the crowdion velocity would be also supersonic that was earlier predicted (A.M. Kosevich and L.S. Kovalyov). An assumption on possible participation of cumulative effect in the process has been made. Виходячи з результатів експериментального вивчення кінетики утворення і морфології пор у монокристалах KCl в умовах оптичного пробою кристала сфокусованим випромінюванням лазера показано, що при спостережуваних параметрах очагів енергетичних спалахів і динаміки їх утворення цей процес аналогічний сильному точковому вибуху. У розігрітій області виникає ударна хвиля. Маючи швидкість більш ніж на порядок вищу за швидкість звуку, ударна хвиля приходить до границі монокристалу раніше за інші пружні збурення решітки, ініціюючи утворення краудіонів і їх рух по щільноупакованих рядах атомів, паралельним напрямам типу <110>, в обох підрешітках. З умови самоузгодження потоків утворення краудіонів, спровокованого надзвуковою ударною хвилею, і їх переміщення в ненапружений кристал витікає, що швидкість руху краудіонів повинна бути також надзвуковою, що передбачалося раніше (А.М. Косевіч, Л.С. Ковальов). Висловлено припущення про можливу участь в процесі кумулятивного ефекту. Основываясь на результатах экспериментального изучения кинетики образования и морфологии пор в монокристаллах KCl в условиях оптического пробоя кристалла сфокусированным излучением лазера, показано, что при наблюдаемых параметрах очагов энергетических вспышек и динамики их образования этот процесс аналогичен сильному точечному взрыву. В разогретой области возникает ударная волна. Имея скорость более чем на порядок выше скорости звука, ударная волна приходит к границе монокристалла раньше других решеточных возмущений, инициируя образование краудионов и их движение по плотноупакованным рядам атомов, параллельным направлениям типа <110>, в обеих подрешетках. Из условия самосогласования потоков рождения краудионов, спровоцированного сверхзвуковой ударной волной, и их ухода в ненапряженный кристалл следует, что скорость движения краудионов должна быть также сверхзвуковой, что предсказывалось ранее (А.М. Косевич, Л.С. Ковалев). Высказано предположение о возможном участии в процессе кумулятивного эффекта.